Correlation between Serum Fatty Acid Binding Protein 4 (FABP4) Levels and Cardiac Function in Patients with Thalassemia Major. (27th December 2021) - Fianza, Pandji I.; Rahmawati, Anita; Afifah, Shofura; Praptama, Suhendra; Ghozali, Mohammad; Sihite, Teddy A.; Setiabudi, Djatnika; Syamsunarno, Mas R. A. A.; Fucharoen, Suthat; Panigoro, Ramdan
Abstract : Background . Patients with thalassemia major may suffer from complications due to iron overload. It has been suggested that several adipokines may play a potential role in the development of complications in thalassemia. Fatty acid-binding protein 4 (FABP4) is one of the adipokines, bridging several aspects of metabolic and inflammatory pathways. Little is known about the relationship between this adipokine and cardiac and liver function, especially in patients with thalassemia major. Aims . This study is aimed at determining serum FABP4 levels in patients with thalassemia major and whether its concentration correlated with serum ferritin levels, as well as cardiac and liver function. Methods . Thalassemia major outpatients (n = 48 ) completed laboratory examination, echocardiography, and electrocardiography. Results . The mean age was 21.9 ± 8.0 years. A negative and weak correlation between serum ferritin and FABP4 was observed (r = − 0.291, p < 0.05 ). In addition, there was moderate and positive correlation between left atrial volume index (LAVI) and FABP4 (r = 0.316, p < 0.05 ). Conclusions . Serum FABP4 correlated with serum ferritin and cardiac function in patients with thalassemia major. FABP4 may be a potential clinical biomarker for cardiac dysfunction via metabolic and inflammatory pathways due to iron accumulation and toxicity in patients with thalassemia major.